Analisis Pengendalian Kualitas Menggunakan Metode Statistical Quality Control (SQC), RCA dan PDCA (Studi Kasus: PT. ABC) - Diona Vita Ayu Ningrum; Herlina Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
In a competitive industrial environment, manufacturing companies are required to produce high-quality products to maintain their market presence and competitiveness. PT. ABC, a manufacturer of CPP and VMCPP films, faced issues with a high product defect rate of 11% in January 2026, which exceeded the company's tolerance standard (<10%). This study aims to analyze quality control using an integrated method of Statistical Quality Control (SQC), Root Cause Analysis (RCA), and Plan-Do-Check-Act (PDCA) to identify root causes and formulate improvement solutions. The results of the study on a total production of 38,582,482 kg revealed 4,604,779 kg of defective products. Slack Band defects were the most dominant type, accounting for 1,144,042 kg (25%). The scatter diagram indicates a positive correlation between production volume and defects, while the p-control chart shows that the process remains statistically controlled despite one out-of-control point. Fishbone diagram and 5 Whys analyses indicate that the primary root causes stem from tension winding instability, machine conditions, operators, SOPs, materials, measuring tools, and the environment.